Desarrollo larval de Prochilodus magdalenae (Steindachner, 1879) (Pisces: Prochilodontidae), río Magdalena, Colombia (2010)
ABSTRACT: Morphological and morphometric descriptions of the larval development of Prochilodus magdalenae, from the Magdalena river, Colombia are provided. Specimens were obtained by induced spawning. This species produces very hydrated free eggs. The incubation period was short; it lasted 14 hours at 24 oC after fertilization. Larvae are slightly developed at hatching, with relatively rapid larval development and an accentuated metamorphosis. Analysis of the morphometric data showed that some parts of the body of P. magdalenae do not grow proportionally.